The Association between Physical Activity Levels and Social Media Addiction among Adolescents: A Descriptive Correlational Study - İbrahim Hakkı Çağıran; Gökhan Dege; Dursun Alper Yılmaz (Türk Spor ve Egzersiz Dergisi, 2023)
The aim of this study is to evaluate the relationship between physical activity levels and social media addiction in adolescents. The study was designed as a descriptive correlational study, and the research group consisted of 160 volunteer students (90 female, 70 male) residing in Agri, Turkey. Two scales were used to collect data: the Social Media Addiction Scale for Adolescents and the short form of the International Physical Activity Questionnaire. The data were analyzed using correlation and regression analysis. The results of the study showed that there was no significant relationship between the physical activity levels of the participants and their social media addiction (p>0.05). However, a strong positive correlation was found between the genders of the participants and their moderate physical activity and total physical activity levels (p 0.05), but a weak positive correlation was found between social media addiction and the age of the students (p < 0.05). The study concludes that there is no significant relationship between social media addiction and physical activity levels in adolescents. However, there is a positive correlation between the genders of the participants and their physical activity levels. These findings may be useful in developing interventions to promote physical activity and reduce social media addiction in adolescents.